Sources of Labor Productivity Growth in the German Brewing Industry - Giannis Karagiannis; Magnus Kellermann; Klaus Salhofer (Universität für Bodenkultur Wien, Department für Wirtschafts- und Sozialwissenschaften, Institut für nachhaltige Wirtschaftsentwicklung, 2019)
We decompose aggregate industry labor productivity growth into seven distinct components: input deepening, technical change, technical efficiency, scale effect, between-firm reallocation, effects from exits and entry. The first four components measure the productivity growth within a firm. The latter three components capture industry dynamics. Applied to a sample of 118 small and medium sized breweries in Germany over 13 years, we found that within-firm effects, in particular technical change and the scale effect, clearly dominated the effects from industry restructuring.
Keywords: D24; J24; L16; O12; 330; labor productivity; productivity growth; structural change; brewing industry; Germany